Nematomorpha from the Philippines, with description of two new species - Schmidt-Rhaesa, Andreas; Schwarz, Christian J. (Zootaxa, 2016)
With the exception of one species, no horsehair worms (Nematomorpha) were known to date from the Philippines. We report here several records, almost all from Panay Island. Two species, Gordius jorriti and Acutogordius finni, are described as new species. Two species of Chordodes, C. caledoniensis and C. cf. moutoni, were found. In addition, further specimens from the genera Gordius, Acutogordius and Chordodes could not be determined to species level.